Professional guideline versus product label selection for treatment with IV thrombolysis: an analysis from SITS registry - Cameron, Alan; Bogie, James; Abdul-Rahim, Azmil H; Ahmed, Niaz; Mazya, Michael; Mikulik, Robert; Hacke, Werner; Lees, Kennedy R (European stroke journal, 2017)
Thrombolysis usage in ischaemic stroke varies across sites. Divergent advice from professional guidelines and product labels may contribute. Patients and methods: We analysed SITS-International registry patients enrolled January 2010 through June 2016. We grouped sites into organisational tertiles by number of patients arriving ≤2.5 h and treated ≤3 h, percentage arriving ≤2.5 h and treated ≤3 h, and numbers treated ≤3 h. We assigned scores of 1-3 (lower/middle/upper) per variable and 2 for onsite thrombectomy. We classified sites as lower efficiency (summed scores 3-5), medium efficiency (6-8) or higher efficiency (9-11). Sites were also grouped by adherence with European product label and ESO guideline: ‘label adherent’ (>95% on-label), ‘guideline adherent’ (≥5% off-label, ≥95% on-guideline) or ‘guideline non-adherent’ (>5% off-guideline). We cross-tabulated site-efficiency and adherence. We estimated the potential benefit of universally selecting by ESO guidance, using onset-to-treatment time-specific numbers needed to treat for day 90 mRS 0-1. Results: A total of 56,689 patients at 597 sites were included: 163 sites were higher efficiency, 204 medium efficiency and 230 lower efficiency. Fifty-six sites were ‘label adherent’, 204 ‘guideline adherent’ and 337 ‘guideline non-adherent’. There were strong associations between site-efficiency and adherence (P < 0.001). Almost all ‘label adherent’ sites (55, 98%) were lower efficiency. If all patients were treated by ESO guidelines, an additional 17,031 would receive alteplase, which translates into 1922 more patients with favourable three-month outcomes. Discussion: Adherence with product labels is highest in lower efficiency sites. Closer alignment with professional guidelines would increase patients treated and favourable outcomes. Conclusion: Product labels should be revised to allow treatment of patients ≤4.5 h from onset and aged ≥80 years.
Gesehen am 23.10.2019